Simple bone cyst: Uncommon cyst of jaw - Gurung, Gopal; Chapagain, Laxmi Prasad; Rokaya, Yagya Bahadur (Birat Journal of Health Sciences, 2020)
Simple bone cyst (SBC) of the jaws is uncommon, representing approximately 1% of all jaw cysts. It is often accidentally discovered on routine dental examination as it is asymptomatic in most of cases. In this report, we discuss a case of SBC in a 16 years old female who presented in our department for correction of her mal-aligned teeth. On routine x-ray for orthodontic treatment, a well defined, unilocular radiolucent area approximately 3x1cm in size with scalloped borders on the left body of mandible expanding from distal surface of 34 to distal surface of 37 was discovered. Surgical exploration was required for both diagnostic and definitive treatment. The operative finding was hollow cavity without any epithelial lining.